PERANAN MAJELIS TAKLIM DALAM PENANAMAN NILAI-NILAI ISLAM DI KECAMATAN LUBUKLINGGAU TIMUR II KOTA LUBUKLINGGAU - Nurlila Kamsi (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2017)
Abstract: This study aimed to describe the activities of Islamic study groups in east Lubuklinggau II in implementing Islamic value. To describe Islamic values to the Islamic study groups , and to describe the implementation or actualization of Islamic values congregation during informal Council in District II East Lubuklinggau. This research used qualitative descriptive approach. In obtaining the data, the authors used observation, interviews, checklists, and documentation. The results of this research indicated that during informal activities in the District Assembly east Lubuklinggau II in planting the values of Islam are: Islamic Teaching (pengajian) regularly carried out once a week, comemoration great day in Islam (PHBI), Conducting and Training the dead bodies in Islamic ways, Conducting for reading Al-Barzanji, held a tambourine exercises, visits to orphanages, Islamic Centre and visit sick members of the congregation, held holding Tasbih prayer beads, and tadarus Al-Qur’an. Islamic values are applied to the Islamic study groups in east Lubuklinggau II in faith, Islam, charity, piety, sincerity, trust, gratitude, patience, friendship, brotherhood, equality, fair, well thought, humble, a promise, gracefully, trustworthy, officer, thrift, and kindness. Implementasi or actualizing values of Islamic congregation during informal Council in District II East Lubuklinggau Lubuklinggau been done properly, pilgrims have solid faith and piety, the faith of the pilgrims have a good life and gave birth to a sincere attitude in addition they also have good morals in dealing with beings Islam. In applying the concept of Islamic values associated with human pilgrims informal gatherings Eastern District of Lubuklinggau II Lubuklinggau often stay in touch, keep the fraternity (brotherhood Islamiyah), was equal or equal before God, to be just, kind thought, humble, just a promise, gracefully, trustworthy, officers, safe and generous.